1986
DOI: 10.1139/z86-176
|View full text |Cite
|
Sign up to set email alerts
|

The avian pectoralis: histochemical characterization and distribution of muscle fiber types

Abstract: The muscle fibers of superficial (ventral) and deep (dorsal) samples from the pectoralis muscle of 43 species of carinate birds are characterized histochemically on the basis of their myofibrillar adenosine triphosphatase (mATPase) activity after acidic and alkaline preincubations. Muscle fibers are described as slow tonic (alkali-labile/acid-stable mATPase activity) or fast twitch (alkali-stable/acid-labile mATPase activity). Three varieties of fast-twitch fibers are recognized histochemically on the basis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
107
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(112 citation statements)
references
References 0 publications
4
107
1
Order By: Relevance
“…Present understanding is that the pectoralis via downstroke provide the majority of the work and power necessary for flapping flight [12,31] even in hummingbirds, where the upstroke contribution during hovering and slow flight is 25-30% of the total lift production [19,20,62,63]. The fibre composition of the pectoralis is remarkably uniform among most species, including only fast-twitch fibres with relatively limited variation in myosin isoforms [64,65]. Exceptions to this pattern are certain soaring birds that exhibit deep accessory bellies composed of slow-twitch fibres [66,67].…”
Section: Muscle Function Proximal To Distal In the Wingmentioning
confidence: 99%
“…Present understanding is that the pectoralis via downstroke provide the majority of the work and power necessary for flapping flight [12,31] even in hummingbirds, where the upstroke contribution during hovering and slow flight is 25-30% of the total lift production [19,20,62,63]. The fibre composition of the pectoralis is remarkably uniform among most species, including only fast-twitch fibres with relatively limited variation in myosin isoforms [64,65]. Exceptions to this pattern are certain soaring birds that exhibit deep accessory bellies composed of slow-twitch fibres [66,67].…”
Section: Muscle Function Proximal To Distal In the Wingmentioning
confidence: 99%
“…Specifically, rat muscles used for mitochondrial isolation consisted of 71.7% fast glycolytic fibers (type IIb), with fast oxidative glycolytic (type IIa) and slow oxidative fibers (type I) constituting the remaining 20.5 and 7.8%, respectively (Armstrong and Phelps, 1984). Sparrow pectoralis is comprised exclusively of fast oxidative glycolytic fibers (George and Berger, 1966;Rosser and George, 1986). …”
mentioning
confidence: 99%
“…This M. pectoralis in volant species mainly consists of red, type IIa, fast oxidative glycolytic (FOG) fibres and a small amount of white, type IIb, fast glycolytic (FG) fibres (Butler 1991). Although George and Berger (1966) claim that ducks have a combination of FG, FOG and SO in the M. pectoralis, the study by Rosser and George (1986) found that the M. pectoralis in Anseriformes (ducks and geese) consists of red, FOG fibres and white, FG fibres. This is believed to be a result of the fast muscle contracting requirements for movement of the wings (Rosser and George 1986).…”
Section: Breastmentioning
confidence: 98%
“…Although George and Berger (1966) claim that ducks have a combination of FG, FOG and SO in the M. pectoralis, the study by Rosser and George (1986) found that the M. pectoralis in Anseriformes (ducks and geese) consists of red, FOG fibres and white, FG fibres. This is believed to be a result of the fast muscle contracting requirements for movement of the wings (Rosser and George 1986). Baeza et al (2000) also reported that the breast muscle of Mule ducks consisted of type IIa (88 %) and type IIb (12 %) muscle fibre types.…”
Section: Breastmentioning
confidence: 98%